Efektivitas E-Parenting Tools Dalam Meningkatkan Pengetahuan Orang Tua Tentang Tumbuh Kembang Anak - Ekayanti, Ekayanti; Sya'bin, Nurul; Hartinah, Asniah; Saputri, Resti Dona; Sriwahyuningsih, Ade; Asli, Kartika; Muldaniyah, Muldaniyah (Madu Jurnal Ilmu Kebidanan, 2025)
In the digital era, the role of parents is crucial in monitoring and stimulating a child's growth and development, which is a golden period that determines the quality of life in the future. E-parenting tools, such as digital applications and online platforms, are technological innovations that facilitate parents in improving their knowledge about this topic. This study aimed to test the effectiveness of e-parenting tools in increasing parents' knowledge about child growth and development. The study used a pre-experimental design with a one-group pretest-posttest approach, involving 30 respondents from Posyandu Melati who were selected through purposive sampling. The respondents were parents of toddlers who could use a smartphone. The research findings show a significant increase in parents' knowledge after using the e-parenting tools. This is proven by the average post-test score (79.83) which was much higher than the pre-test score (62.67). Statistical analysis using a Paired t-test yielded a significance value (p-value) of 0.000, which is below the 0.05 threshold